Psychometric Properties of the Suicidal Ideation Scale in the Indonesian Language. (December 2022) - Fitriana, Efi; Purba, Fredrick Dermawan; Salsabila, Safira Putri; Danasasmita, Febrianti Santiardi; Afriandi, Irvan; Tarigan, Rodman; Ichsan, Abdullah; Pandia, Veranita
Introduction: Suicide is one of the leading cause of mortality among adolescents and young adults, especially in low to middle-income countries. Research found that screening for suicidal ideation in non-clinical populations such as schools or communities is an important step toward preventing suicide. Despite so, not all screening tools have the capabilities to accurately detect suicidal ideation among adolescents and young adults in non-clinical populations. The Suicidal Ideation Scale (SIS) is one of the most used questionnaires to measure suicidal thoughts in non-clinical populations. This study aims to investigate the psychometric properties of SIS among adolescents and young adults in Indonesia, especially in non-clinical populations. Methods: After a series of language and cultural adaptations, 1254 senior high school and university students completed the Indonesian version of SIS using 3 standard questionnaires, namely Patient Health Questionnaire-9/PHQ-9, Beck Depression Inventory-II/BDI-II, and Children's Depression Inventory/CDI. The SIS content validity, internal consistency, test-retest reliability and concurrent, as well as internal structure validity, were investigated using content validity index (CVI), Cronbach's Alpha, Pearson product-moment correlation, and confirmatory factor analysis (CFA), respectively. Results: The result showed that SIS has good to excellent internal consistency and test-retest reliability. Based on the validity indicators, it has satisfactory content and convergent validity, and further support the one-factor and 2-factor model for factorial validity. Both one-factor and 2 factor model are suitable to use in non-clinical settings. Conclusions: SIS is a valid and reliable tool for suicide ideation screening in adolescents and young adults in non-clinical populations. This validated questionnaire can be used in the early detection of suicidal ideation among adolescents and young adults in non-clinical populations, thus contributing to developing strategies and policies to prevent suicide among Indonesian adolescents and young adults at group and institutional levels.